THE FUTURE OF COMPUTER ASSISTED EDUCATION (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2021)
The objective of this study is to investigate and drill down into the innovative method of teaching aided by computers and their technology. It sheds light on the new invention of computer-assisted education and its current efficacy. The use of a computer and related gadgets in education is referred to as computer assisted education. It does not imply that instructors will be replaced, but rather that teachers will use computer equipment and software to educate, such as smart courses, videos, and web coaching. This research demonstrates how, in the face of an outbreak, we concentrate just on computer-assisted instruction. Without computer-assisted schooling nowadays, we would not have been able to explore or obtain an education. The technological innovation of computer-assisted teaching has been readily welcomed by the globe. The purpose of this study is to examine the effectiveness of computer-assisted education.
Keywords: Education; Teachers; Smart classes; Videos; Technology